ONLINE EDUCATION PROGRAM POLICIES TOWARD TEACHER TEACHING ABILITY AND LEARNING PROCESS IN PRIMARY SCHOOL (Universitas Negeri Semarang, 2019)
Teacher competency is a mandatory requirement of every individual who works as a teacher at the lowest level such as PAUD or skill subject teacher at the high school level, and here even the Class Teachers in Elementary School must have because it is a pedagogic competence that is one of the four competencies that must be owned by a teacher in accordance with the Teacher and Lecturer Law. The right way to improve professional teacher competency is by coaching, training or non-training / activities other than education and training and is now rife with development through education / education in the network or known online. With this Online it is clear that the ability of a teacher in the use of technology need not be doubted, because all the training processes are carried out and completed with the use of computers. So that the computer capabilities of the teacher must be in good category. This study aims to assess the teaching ability of teachers and the learning process in the classroom by comparing several classes of teachers who obtain online and have not received education training in the network. The results of the study are analysis data obtained from students with the help of questionnaires, teacher teaching skills in designing learning and in preparing learning tools. This research is a qualitative descriptive study. The results show that there are errors in alternative learning carried out in the classroom, that learning is still in flattening rather than integrated. Therefore it is necessary to improve the evaluation in online activities held by the government, because in the value of the teacher evaluation is complete, but the skills and ability to teach teachers can not meet the national education goals. Not only that?, the transition from the two different curricula? is still widely found learning can not meet the scientific approach criteria